2018
DOI: 10.1007/s13202-018-0454-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of multi-layered commingled and compartmentalized gas reservoirs

Abstract: The evaluation and performance prediction of multi-layered compartmentalized gas systems can be difficult. This is mostly due to the uncertainties related to production allocation either within each commingled well or between interrelated reservoir compartments. This paper presents a model that can provide reliable estimates of the total gas in place for multi-layered commingled and compartmentalized reservoirs. The model is also capable of generating prediction profiles for every well in the production system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…2696 × 10 8 πr 2 ej h j ϕ j S gij /T ij (12) where P ij is the original reservoir pressure of layer j, MPa; Z ij is the deviation factor corresponding to P ij ; T ij is the temperature of the reservoir, K; G pj is the cumulative gas production of layer j, 10 8 m 3 ; G ij is the controlled reserves of layer j, 10 8 m 3 ; S gij is the initial gas saturation of layer j; ϕ j is the porosity of layer j. Substitute Equation ( 12) into Equation ( 11):…”
Section: Calculation Model Of Drainage Radius Of Multi-layered Gas Wellmentioning
confidence: 99%
See 2 more Smart Citations
“…2696 × 10 8 πr 2 ej h j ϕ j S gij /T ij (12) where P ij is the original reservoir pressure of layer j, MPa; Z ij is the deviation factor corresponding to P ij ; T ij is the temperature of the reservoir, K; G pj is the cumulative gas production of layer j, 10 8 m 3 ; G ij is the controlled reserves of layer j, 10 8 m 3 ; S gij is the initial gas saturation of layer j; ϕ j is the porosity of layer j. Substitute Equation ( 12) into Equation ( 11):…”
Section: Calculation Model Of Drainage Radius Of Multi-layered Gas Wellmentioning
confidence: 99%
“…Bela et al [11] extended the DTM method to the horizontal wellbore model in order to obtain individual layer permeabilities and skin factors of stratified reservoirs with multilateral wells. Sallam and El-Banbi [12] and Juell and Whitson [13] attempted to analyze multi-layered commingled gas reservoirs using an iterative workflow. Although they achieved history in the matching of gas wells or gas reservoirs through continuous iteration, these methods have multiple solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional analytical solutions cannot accurately characterize heterogeneity nor seepage [23][24][25][26]. Moreover, many experiments have shown that there are mechanisms such as high-speed non-Darcy seepage, stress sensitivity, movable water flow, and aqueous-phase nonlinear percolation in tight gas reservoirs, which cannot be accurately described by traditional analytical solutions [27,28]. Therefore, this paper takes Block A in the Xihu Sag of the East China Sea Basin as the research object.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have proposed many new production splitting methods on the basis of various mathematical theories and basic seepage laws [20][21][22][23][24]. Hu et al used grey relational analysis to analyze the various weights that affect the split of production [25].…”
Section: Introductionmentioning
confidence: 99%